THE EFFECTIVENESS OF USING SMALL GROUP DISCUSSION ON STUDENTS' SPEAKING SKILL - Christin Natalia Hutagalung; Ira Tresnawati Sitorus (UIBU, 2020)
In learning English, students should acquire the four skills that are reading, writing,listening and speaking. These four skills are abilities that are mandatory for everyone who wants to learn English. Specifically speaking.Speaking is quite important to be owned to students.It is also statedin the English syllabus of Curriculum 2013 (K-13) require students to be able to express and response some kinds of expression orallyin English.In reality, many students are still poor in speaking English.Researcher use quantitative data. Based on the way data is collected, quantitative data can be divided into two, namely discrete data and continuum data. From the characteristics of the data, quantitative data can be in the form of various types of data, namely nominal data, ordinal data, interval data and ratio data. That way, in this study, researchers used quantitative data, this is because the characteristics are in accordance with the research conducted this time.In quantitative data the resulting data will be in the form of numerical data which will later be processed in accordance with procedures that have been submitted using quantitative data calculations. The process of collecting data in this study will be carried out by pre-test and post-test methods.And from the results of the analysis, researchers found and concluded that there was no significant impact between teaching with small group discussion strategies and without small group discussion strategies.